Reaching Out in a Networked World: Expressing Your Congregation's Heart and Soul - Baab, Lynne M. (Rowman & Littlefield Publishers, 2008)
A congregation communicates its heart and soul through words, photos, actions, programs, architecture, decor, the arts, and countless other aspects of congregational life. In Reaching Out in a Networked World, communications expert and pastor Lynne Baab examines technologies such as websites, blogs, online communities, and desktop publishing. She demonstrates how a congregation can evaluate these tools and appropriately use them to communicate its heart and soul, to convey its identity and values both within and outside the congregation. Baab urges congregation leaders to reflect on the way they communicate. The recent explosion in communication technologies offers many new ways to present values and identity, but no one has much experience thinking about how best to use these tools. Baab seeks to help leaders use these new technologies with more precision, flair, and consistency. When congregations are intentional about communicating who they are and what they value, people in the wider community can get a clear and coherent picture of the congregation and its mission. Newcomers and visitors are more likely to see why faith commitments matter and why and how they might become involved in this congregation, while current members and leaders will greatly benefit from having a unified vision of the congregation's heart and soul.